Physical and Behavioral Health of Health Science Students of a Medical College of Nepal during COVID Pandemic - Mahotra, Narayan Bahadur; Kandel, Sabita; Gurung, Sanyukta; Joshi, Bishal (Med Phoenix, 2022)
Introduction Worldwide pandemic of COVID 19 and its confinement has affected in some way the physical and behavioral aspect of every individual. Health science students are generally known to have reduced physical activity and decreased sleep duration. During the COVID pandemic health science students may adapt different health behavior because of their knowledge about the healthy behaviors. This study aims to explore the physical and behavioral health of health science students of Maharajgunj Medical Campus, and Maharajgunj Nursing Campus during COVID pandemic in Nepal. Methods A descriptive cross-sectional study was conducted from February 2021 to June 2021 using self-structured questionnaires to examine the students in two domains (i) Physical health (ii) Behavioral health. A convenience sampling was used. 146 students were enrolled in the study. Statistical analysis was done using SPSS version 25. Results The study revealed that 63% of the participants exercised during the pandemic. Majority of the female participants had change in eating pattern (65%) and sleeping pattern (60.3%) while majority of male reported no change in eating pattern (52.4%) and sleeping pattern (60.3%). Majority of both males (70%) and females (85.2%) consumed nutritious food during the pandemic. 98.8% females and 100% males used face mask and maintained physical distance while outdoor. Fewer participants with cough and fever (64.9%) self-isolated while majority used face mask (97.3%), covered mouth while coughing (94.6%) and maintained physical distance (81.1%). Conclusion COVID pandemic was known to affect the physical health of health science students and they also adapted different behaviors during the pandemic.